A review of appendectomy cases at a single teaching hospital, Baghdad, Iraq - Abdullah, Mohanad Hamed; Saood, Mahmood J.; Tawfiq, Naser R. (International Surgery Journal, 2017)
Background: Appendectomy is one of the most commonly performed operations. Accurate preoperative diagnosis has long been a great challenge, even to experienced surgeons. To determine the pattern of presentation and rate of atypical pathological presentation of appendicitis. Methods: This is a cross-sectional study in which patients who underwent appendectomy for presumed acute appendicitis from June 2012 to June 2016 were recruited. Incidental appendectomy was excluded. Patient demographics, pathological findings, and surgical outcomes were collected. Results: It was found that the median age of the patients with acute appendicitis was 29 (male 27.3, female 30.7; range (4-67) years. The median length of hospital stay was 2 (range, 1-22) days. There were 184 (75%) patients with clinically and pathologically confirmed acute appendicitis. Out of the 243 patients, 47 appendices were normal, making the overall negative appendectomy rate (NAR) 19.3%; 14.0% in males and 24.6% in females (P<0.001). Conclusions: Appendectomy continues to be a very common surgical procedure. We suggest a more liberal utilisation of preoperative imaging in females of reproductive age, and patients at the extreme age.